Performance of Chitosan and Polyglutamic Acid in Palm Oil Mill Effluent Treatment - Lee, Mandjun; Lee, P. S. (Engineering Science Reference, 2020)
This chapter presents the study on pollutant removal efficiency in palm oil mill effluent using chitosan and polyglutamic acid (PGA). Up until today, palm oil mill effluent (POME) has been considered one of the significant sources of environmental pollution. The characteristics of POME include contaminating the source of drinking water, which is also harmful to the aquatic ecosystem by creating a highly acidic environment or causing eutrophication. With increasing public awareness of environmental pollution, it creates the need to address this issue. Both chitosan and PGA are non-polluting food-based anionic and biodegradable biopolymers that are environmentally friendly in wastewater treatment. The critical parameter to determine the effectiveness of pollutants removal is chemical oxygen demand, colour, and total suspended solids. In this aspect, this chapter also discussed some of the significant findings done in previous studies to provide proper understandings and implications on this topic.